EU counter-terrorist policies and fundamental rights the case of individual sanctions - Eckes, Christina (Oxford : Oxford University Press, 2010)
This work examines the issues arising from the European Union's practice of listing and sanctioning individuals suspected of supporting terrorism. It provides a comprehensive analysis of the complex legal problems involved, and the difficulty of safeguarding suspects' rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sanctions (Law) -- European Union countries; Terrorism -- European Union countries -- Prevention; Human rights -- European Union countries